1994
DOI: 10.1002/pola.1994.080320613
|View full text |Cite
|
Sign up to set email alerts
|

1H‐NMR and UV studies of Rh complexes as a stereoregular polymerization catalysts for phenylacetylenes: Effects of ligands and solvents on its catalyst activity

Abstract: Phenylacetylene and its homologues bearing methoxy or chloro groups in the para position of the phenyl ring were stereoregularly polymerized by Rh complex catalysts, e.g., [Rh (norbornadiene) Cl]2, in the presence of various solvents. The 1H‐NMR and UV study of the Rh complex showed that the activity of the Rh catalysts greatly depends upon not only the ligand in the Rh catalyst but also on the solvent used, e.g., polyphenylacetylene with a highly cis‐transoidal content was quantitatively obtained when norborn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
135
1

Year Published

1997
1997
2001
2001

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 141 publications
(140 citation statements)
references
References 18 publications
(5 reference statements)
4
135
1
Order By: Relevance
“…We have reported 12,13,15,16,18) that the Wilkinson type catalysts, such as [Rh(L-L)Cl] 2 , L-L = norbornadiene (NBD) or cyclooctadiene (COD), are extremely effective for the formation of aromatic polyacetylenes (Scheme 2) to produce the corresponding cis-transoid polyacetylenes, when amine or alcohol was used as the solvent under mild conditions (Tab. 1).…”
Section: Stereospecific Polymerization Of Aromatic Acetylenesmentioning
confidence: 99%
See 3 more Smart Citations
“…We have reported 12,13,15,16,18) that the Wilkinson type catalysts, such as [Rh(L-L)Cl] 2 , L-L = norbornadiene (NBD) or cyclooctadiene (COD), are extremely effective for the formation of aromatic polyacetylenes (Scheme 2) to produce the corresponding cis-transoid polyacetylenes, when amine or alcohol was used as the solvent under mild conditions (Tab. 1).…”
Section: Stereospecific Polymerization Of Aromatic Acetylenesmentioning
confidence: 99%
“…On the other hand, using the [Rh(NBD)Cl] 2 catalyst at room temperature produces the cis-isomer almost quantitatively, forming light yellow and amorphous material bearing a fairly high molecular weight when poor solvents such as alcohol or amine were used in the polymerization. We found that the most outstanding features of the resulting polyacetylene, which was stereospecifically prepared using the simple Rh complex catalyst, are first: 1 H and 13 C NMR spectra of the resulting polymers have extremely sharp line widths compared with those of the trans-isomers 16,18,20) , which makes an unequivocal assignment of each signal impossible and may be correlated with the polymer structures and/or the concentration of p-radicals involved in the trans-conjugated polymer [23][24] and second: the formation of a pseudohexagonal, columnar structure, representing self-assembly or a superstructure, which is associated with useful and anisotropic physicochemical properties 19,20) . Therefore, these characteristics may be a proof of the highly stereospecific polymerization of monosubstituted acetylenes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 It has been proposed that the effect of the solvents is to promote In a previous article we reported that phenylacetthe efficient dissociation of the dimer complex ylene (PA), 1 its homologues, 2 a-naphthylacety-[Rh(NBD)Cl] 2 into the monomeric species, which lene, 3 and alkylpropiolates, 4,5 and pentynoate 6 may be an important initiation species for this can be stereospecifically polymerized in the prespolymerization, 1,7 as shown in Scheme 1. Further, ence of a Rh complex, [Rh(norbornadiene)Cl] 2 , the structural differences observed between poly-[Rh(NBD)Cl] 2 , when triethylamine (TEA) or an pentynoates prepared with the Rh complex cataalcohol is used as the polymerization solvent and lyst and with metathesis catalysts such as WCl 6 that the helical cis-transoid isomer were selecwas interpreted in terms of the difference in geotively formed in high yields under mild conditions.…”
Section: Introductionmentioning
confidence: 98%